Adult education without a soul? Colonialism, economic progress, and democratic underdevelopment in Hong Kong - John Holford (Adult Education Research Conference, 1994)
Key moments in the evolution of adult education in Hong Kong are explored: these shed light on the relationship between adult education, economic development, and democratisation under late colonialsim.